Crystallographic and Theoretical Evidences of Anion⋅⋅⋅Anion Interaction. Issue 9 (6th April 2021) - Wysokiński, Rafał; Zierkiewicz, Wiktor; Michalczyk, Mariusz; Scheiner, Steve
Abstract: Planar (HgCl3 ) − anions are stacked fairly closely together in a slipped parallel arrangement within several crystal structures. Quantum chemical analysis shows evidence of strong noncovalent spodium bonds between the Hg π ‐hole of one unit and the Cl atom of an adjacent unit. Anion⋅⋅⋅anion spodium bonds work in tandem with crystal packing forces. Abstract : Combined experimental and theoretical analysis elaborates on a new idea in noncovalent bonding (namely, spodium bonding) linking two anionic subunits. This counterintuitive interaction involves Hg atoms as electron‐density acceptors.